Study of morphological characteristics on hydrophilicity‐enhanced SiO2/Nafion composite membranes by using multimode atomic force microscopy. (29th April 2019) - Son, Byungrak; Oh, Kwangjin; Park, Sam; Lee, Tae‐Gwan; Lee, Dong Ha; Kwon, Osung
Summary: Air‐breathing proton exchange membrane fuel cells (AB‐PEMFCs) have a great potential for commercialization owing to their simple mechanical configuration and low cost compared with traditional proton exchange membrane fuel cells (PEMFCs). However, AB‐PEMFCs perform worse than traditional PEMFCs owing to the omission of the humidifier and a poor air supply system. In this study, hygroscopic metal oxide materials with good water absorption characteristics were employed in a Nafion membrane without humidification to compensate for the lack of performance owing to low proton conductivity. Among the various metal oxide materials, mesoporous structured silica has been synthesized with Nafion to increase the water content in nonhumidified conditions. The local morphological variation and surface charge distribution on the pristine Nafion and SiO2 /Nafion composite membranes were analyzed by using multimode atomic force microscopy and force distance analyses. Several remarkable results were revealed, including considerable morphological changes and a locally separated water cluster network structure.